Public Policies for the Digitalization of Public Services in the European Union: From Foundations to Contemporary Challenges - Gherghin, Claudia-Anamaria (Technium Social Sciences Journal, 2025)
This article examines the digitalization of public services within the European Union (EU), focusing on its institutional, technological, and socio-political aspects. The EU has prioritized e-government to enhance administrative efficiency, transparency, and citizen engagement. Benchmarking tools like the E-Government Development Index (EGDI) and the Digital Economy and Society Index (DESI) are highlighted as key measures for assessing progress across member states. Case studies from countries such as Estonia, Greece, Italy, and Romania reveal significant variations in digital readiness, infrastructure, and governance. The paper emphasizes the importance of collaborative governance, transparency, and open government in building public trust and advancing digital transformation. It also addresses challenges including corruption, gaps in digital literacy, and ethical concerns in the use of automated decision-making. The COVID-19 pandemic's role in accelerating digital initiatives is discussed, along with policy recommendations aimed at improving interoperability, fostering digital skills, and aligning national recovery plans to achieve inclusive and efficient digital governance.